Hybrid βΩ-Indexing Fractal Slotted Multiband Antenna for Electronics Wireless Sensor Applications - Shindhja, N.M.Mary; Varshney, Atul (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
In this proposed work a compact, low profile, inset-fed βΩ-space-filling curve-based slotted fractal antenna for multi-band wireless applications and narrow band operations is designed, fabricated, and successfully tested. The measured results of the reflection coefficient and E-plane and H-plane gain radiation patterns are found to be very concord with simulated corresponding results. The antenna resonates at five resonance frequencies 1.91GHz (1.86-1.93GHz), 3.12GHz (3.03-3.21GHz), 5.56GHz (5.50-5.60GHz), 10.75GHz (10.55-11.20GHz) and 13.94GHz (13.72-14.17GHz) with narrow band. Therefore the proposed antenna is adopted for the applications like PCS-1900 (n2 band: 1850-1910MHz), rail mobile radio (1900-1910MHz), DCS-IMT gap (n98/n39 band: 1880-1920MHz), WCDMA (1900MHz), X-band (10.55-11.20GHz) and Ku-band (13.72-14.17GHz) applications. The antenna parameters gain, directivity, and efficiency are greatly improved by the 50% reduction in ground length. A Good impedance matching is achieved by the use of inset feeding with a 50Ω port at an operating frequency 3.1GHz. The antenna exhibits 2.94dBi gain at the operating frequency. A new hybrid βΩ- space-filling curve has been utilized for the slotted fractal proposed antenna design. The antenna is fabricated on an FR4 substrate with compact dimensions (39.05mm x 32.25mm x 1.6mm) at a frequency 3.1GHz.